The Effect of Earnings Growth, Audit Quality, Investment Opportunity Set on Earnings Quality of Financials Sector Companies on the Indonesia Stock Exchange - Aureliano G T B WIJAYA; Hendrik GAMALIEL; Robert LAMBEY (Journal of Governance, Taxation and Auditing, 2023)
This study aims to examine the effect of earnings growth, audit quality, and investment opportunity set on earnings quality in financial sector companies on the Indonesia Stock Exchange for the 2016-2020 period. Earning growth variable is measured by the earnings growth index, audit quality is measured by the dummy variable, the investment opportunity set is measured by MVBVA, and earnings quality is measured by QER. This type of research is a quantitative effect research using secondary data. The sampling technique used was non-probability sampling with a purposive sampling method which resulted in 34 companies as research samples from 103 companies. The data analysis technique in this study is multiple linear regression using the SPSS 26 program. The partial results show that earnings growth has a significant and positive effect on earnings quality, and audit quality and investment opportunity set have no effect on earnings quality. The results of the study simultaneously show that earnings growth, audit quality, and investment opportunity sets affect earnings quality.